2020
DOI: 10.1515/cclm-2020-1414
|View full text |Cite
|
Sign up to set email alerts
|

IFCC Interim Guidelines on Biochemical/Hematological Monitoring of COVID-19 Patients

Abstract: Routine biochemical and hematological tests have been reported to be useful in the stratification and prognostication of pediatric and adult patients with diagnosed coronavirus disease (COVID-19), correlating with poor outcomes such as the need for mechanical ventilation or intensive care, progression to multisystem organ failure, and/or death. While these tests are already well established in most clinical laboratories, there is still debate regarding their clinical value in the management of COVID-19, partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
35
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 60 publications
5
35
0
1
Order By: Relevance
“…European Society of Cardiology (ESC) recognizes that the strong and consistent association of troponin with death in patients infected by SARS‐CoV‐2 reported in the literature should be seen in favour of this approach, but it concludes that, at this point of time, it is unlikely that cardiac troponin provides incremental value to a predictive model including other strong predictors of death, such as older age, D‐dimer or lymphocyte count and that no specific therapeutic intervention can be justified based on the use of cardiac troponin as a prognostic marker 15 . However, the measurement of cardiac troponin for prognosis of severity in patients with COVID‐19 is supported in other international guidelines and expert recommendations 11,16 . Hence, taken together with electrocardiogram and the clinical assessment, elevation of cardiac troponin levels can inform about ischaemic and nonischaemic causes of myocardial injury related to COVID‐19, which may be associated with a poorer prognosis 17 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…European Society of Cardiology (ESC) recognizes that the strong and consistent association of troponin with death in patients infected by SARS‐CoV‐2 reported in the literature should be seen in favour of this approach, but it concludes that, at this point of time, it is unlikely that cardiac troponin provides incremental value to a predictive model including other strong predictors of death, such as older age, D‐dimer or lymphocyte count and that no specific therapeutic intervention can be justified based on the use of cardiac troponin as a prognostic marker 15 . However, the measurement of cardiac troponin for prognosis of severity in patients with COVID‐19 is supported in other international guidelines and expert recommendations 11,16 . Hence, taken together with electrocardiogram and the clinical assessment, elevation of cardiac troponin levels can inform about ischaemic and nonischaemic causes of myocardial injury related to COVID‐19, which may be associated with a poorer prognosis 17 …”
Section: Discussionmentioning
confidence: 99%
“…Cardiac troponin is a well‐known marker of myocardial injury 7 . Previous recent studies have demonstrated the association of myocardial injury, characterized by elevated cardiac troponins, with COVID‐19 severity in Western multicentre cohorts 8 and single‐centre studies, 9,10 and its measurement has been recommended for prognosis of these patients as indicative of a worsening clinical scenario 11,12 . However, to our knowledge, no study has evaluated the implications of using sex‐specific thresholds, as recommended, 13 to define myocardial injury.…”
Section: Introductionmentioning
confidence: 99%
“…The elevation of serum levels of inflammatory markers is commensurate with the severity of the disease and in some cases increases up to 12 times the reference value, possibly being related to the direct damage to the hepatic tissue or as a secondary effect of the pharmacological treatment used during the hospitalization of patients that evolve toward liver injury (52). For this reason, it is recommended at least to determine the levels of ALT, bilirubin and albumin during the treatment of patients with hepatotoxic medication and those with preexisting hepatic conditions (72).…”
Section: Discussionmentioning
confidence: 99%
“…However, viral etiology is less commonly associated with elevated white blood cell counts than bacterial pneumonia. In the case of SARS-CoV-2 infection, for example, lymphopenia (often associated with eosinophylopenia and piastrinopenia) has been correlated with more severe outcomes ( 22 ). A correlated marker is the neutrophil/lymphocyte ratio (NLR) which, although not specific, is often increased in severe forms of viral pneumonia and was recently proposed as an early risk stratification marker also for COVID-19 patients ( 23 ).…”
Section: Clinical and Laboratory Features Of Respiratory Viral Infectionsmentioning
confidence: 99%